Expression of neuronal nitric oxide synthase splice variants in atherosclerotic plaques of apoE knockout mice - Schödel, Johannes; Padmapriya, P.; Marx, Alexander; Huang, Paul L.; Ertl, Georg; Kuhlencordt, Peter J. (Atherosclerosis, 2009)
Objective: We previously reported that deletion of brain type neuronal nitric oxide synthase-α (nNOS-α) accelerates atherosclerosis in apolipoproteinE (apoE) knockout (ko) mice. The regulation of nNOS expression is complex, involving the generation of mRNA splice variants. The current study investigates occurrence and distribution of nNOS variants in atherosclerotic lesions of apoE ko and apoE/nNOS-α double ko (dko) animals. Methods: Mice were fed a high fat diet for 20 weeks. Immunohistochemistry and western blot analysis were performed using antibodies detecting the carboxy terminal-, or amino terminal-residue of the nNOS protein. Confocal microscopy and in situ hybridization were used to identify the compartment of cellular expression. Results: In situ hybridization revealed the presence of nNOS-α and -γ mRNA variants in apoE ko plaques, while only nNOS-γ was detectable in apoE/nNOS dko plaques. Consistent with mRNA expression nNOS-α protein can be detected in the neointima of apoE ko, but not apoE/nNOS dko animals. In contrast, the carboxy terminal antibody stained the neointima and media in apoE ko vessels and showed residual nNOS immunoreactivity in apoE/nNOS dko lesions. Confocal microscopy showed predominant nNOS expression in vascular smooth muscle cells, while colocalization with macrophages was less pronounced. Conclusions: Our study shows that nNOS-α and -γ splice variants are expressed in atherosclerotic plaques of apoE ko mice. nNOS variants colocalized with markers for vascular smooth muscle cells and macrophages but not for endothelial cells. Since nNOS-α is atheroprotective, other nNOS splice variants which differ in enzyme kinetic and subcellular localization may also influence plaque formation. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Atherosclerosis; Neuronal nitric oxide synthase; Nitric oxide; nNOS variants; Splice variants